Zarządzanie zapasami z uwzględnieniem ryzyka czasu dostaw i jego wpływ na wartość przedsiębiorstwa - Michalski, Grzegorz (Inventories management, delivery risk and value of the firm, 2005)
Maximization of wealth of his owners is the basic financial aim in management of enterprise. Inventories management which control risk contributes to realization this aim. Article presents accessible for enterprises methods which control delivery risk in inventories management decision making by firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 285-296